2018
DOI: 10.3991/ijim.v12i7.9711
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Knowledge and Attitude towards Technology Gadget Usage with Students’ Socio-Emotions Development

Abstract: <p class="0abstract">Gadgets nowdays become one of the most important necessities in human life. The use of gadgets is not only becomes a widespread among adults, but the younger generation also being exposed to this diverse technology gadgets. The gadgets usage among younger generation contributes to the numerous impacts on their socio-emotional development whether in negative or positive ways. Therefore, this study aims to investigate the relationship between knowledge and attitude, towards technology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…The finding shows that the respondents' knowledge level affects their attitude. Similarly, a study by Ashari, Ngadiman, Zainudin, & Jumaat (2018) revealed that students with positive Knowledge about technology had a positive attitude towards its use in learning. Moreover, the respondents' level of knowledge influences their practices.…”
Section: Resultsmentioning
confidence: 95%
“…The finding shows that the respondents' knowledge level affects their attitude. Similarly, a study by Ashari, Ngadiman, Zainudin, & Jumaat (2018) revealed that students with positive Knowledge about technology had a positive attitude towards its use in learning. Moreover, the respondents' level of knowledge influences their practices.…”
Section: Resultsmentioning
confidence: 95%
“…Attitudes are commonly shaped through direct exposure, emulation, incentivization, and social learning. According to research [51], students' attitudes toward technology have an impact on their socio-emotional development. Attitude is a variable psychological structure rather than a static state.…”
Section: Student's Attitude In the Context Of Innovative Learning Toolsmentioning
confidence: 99%
“…It has been shown by (Ashari et al, 2018) that persons who own gadgets have a more favorable attitude toward technological advancements. The knowledge and skill competencies of individuals are also a part of the Facilitating Conditions component.…”
Section: Test For Goodness Of Fitmentioning
confidence: 99%